Determinants of CAT (COPD Assessment Test) scores in a population of patients with COPD in central and Eastern Europe: The POPE study. (April 2019) - Miravitlles, Marc; Koblizek, Vladimir; Esquinas, Cristina; Milenkovic, Branislava; Barczyk, Adam; Tkacova, Ruzena; Somfay, Attila; Zykov, Kirill; Tudoric, Neven; Kostov, Kosta; Zbozinkova, Zuzana; Svoboda, Michal; et al.
Abstract: Background: The COPD Assessment Test (CAT) has been proposed to help guide therapy in chronic obstructive pulmonary disease (COPD). It is important to understand the distribution of scores in different COPD populations and their determinants. Methods: The POPE study is an international, observational cross-sectional study of COPD subjects in 11 Central and Eastern European countries aimed at characterizing COPD phenotypes. Here we report the analysis of CAT scores with the objective of identifying their determinants, evaluating symptom load and investigating the distribution of scores among the participating countries. Additionally, we investigated the discrepancies between the CAT and modified Medical Research Council (mMRC) scores when used to classify patients according to the GOLD strategy. Results: The study included 3452 patients (69.2% men, mean forced expiratory volume in 1 s (FEV1% predicted) 52.5%). The mean CAT score was 17.5 (SD = 7.8), ranging from 15.1 in Hungary to 21.2 in Bulgaria. Multiple linear regression analysis showed six variables significantly associated with CAT scores: depression, number of previous exacerbations, 6-min walking distance, FEV1(%), mMRC and country and explained 47.2% of the variance of CAT. According to either CAT or mMRC, up to 23.9% patients would be classified in different GOLD groups. Conclusions: The CAT score may be predicted by factors related to COPD severity, depression and exercise capacity, with significant differences in the distribution of CAT scores in different countries. According to our results CAT >10 is not equivalent to mMRC >2 for assessing symptom burden. Trial Registration:ClinicalTrials.gov, identifier NCT02119494; Highlights: CAT scores are different in patients from countries of Central and Eastern Europe. CAT is related to depression, exacerbations, FEV1(%), dyspnoea and country. CAT and mMRC scores classify up to 23% of patients in different GOLD categories.